2011
DOI: 10.1016/j.cryobiol.2011.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Activity of bone morphogenetic protein-7 after treatment at various temperatures: Freezing vs. pasteurization vs. allograft

Abstract: The material extracted from the human femoral bone was treated, and the amount of BMP-7 8 was analyzed using an enzyme-linked immunosorbent assay. Then, the activity of 9 recombinant human BMP-7 after the treatment was assessed using a bioassay with NIH3T3 These results suggested that freezing possibly preserves osteoinductive ability than 18 hyperthermia treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
52
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 67 publications
(54 citation statements)
references
References 24 publications
0
52
0
1
Order By: Relevance
“…These are also seen, although less frequently, with frozen autografts; we experienced only three fractures and two non-unions in the present series. This is because autogenous proteins, growth factors, and cytokines are preserved in the frozen bone [22], which could induce good osteoinduction and osteoconduction to achieve satisfactory bone union and revitalization without eliciting an immune reaction. In addition, there is a perfect fit enabling easy and rigid fixation using simple osteosynthesis techniques and avoiding mal-or non-union.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These are also seen, although less frequently, with frozen autografts; we experienced only three fractures and two non-unions in the present series. This is because autogenous proteins, growth factors, and cytokines are preserved in the frozen bone [22], which could induce good osteoinduction and osteoconduction to achieve satisfactory bone union and revitalization without eliciting an immune reaction. In addition, there is a perfect fit enabling easy and rigid fixation using simple osteosynthesis techniques and avoiding mal-or non-union.…”
Section: Discussionmentioning
confidence: 99%
“…In bone retrieved more than a year after implantation, osteocytes and osteoblasts were observed in broad portions of the frozen autograft, and the cortical host-graft junction showed incorporation along with continuity of bone trabeculae, indicating the onset of osteogenesis in the frozen autograft at an early stage. It may be the case that, as mentioned above, frozen bone preserves bone morphogenetic protein and its osteoinductive ability better than hyperthermic treatments such as autoclaving and pasteurization [22]. Furthermore, if the pedicle-freezing procedure method, which is a specific procedure of frozen autografts and distinguishes from other recycled bone, is possible, the number of osteotomy sites can be decreased, allowing for a faster bone union [25].…”
Section: Discussionmentioning
confidence: 99%
“…Takata et al reported that bone morphogenetic activity was better preserved in frozen autografts treated with liquid nitrogen than in those treated by autoclaving or pasteurization [24].…”
Section: Discussionmentioning
confidence: 99%
“…Intercalary reconstruction with the use of a frozen autograft has many advantages; it is a relatively simple and low cost technique, allows a precise fit between the graft and host bone, preserves osteoinduction and osteoconduction [24], averts graft rejection, avoids the transmission of infectious diseases, preserves the bone stock and biomechanical strength, allows easy attachment of ligaments and tendons to bone, prevents harmful denaturation of substances and provides early revitalization with possible cryoimmunological effects [17].…”
Section: Discussionmentioning
confidence: 99%
“…That includes simple procedure without any specific equipment and complicated temperature control; strength of treated bone and superior osteo-conductive and osteo-inductive capacity with spared matrix proteins and enzymes; best compatibility of size and form and attachment of soft tissues such as ligaments and tendons [2,3,11]. These advantages could lead to more preferable bone regeneration and limb functions.…”
Section: Characteristics Of Liquid Nitrogen-treated Bonementioning
confidence: 99%